PELAKSANAAN PEMBERIAN REMISI BAGI NARAPIDANA TINDAK PIDANA KORUPSI SEBAGAI SALAH SATU HAK WARGA BINAAN PEMASYARAKATAN - Novendra Novendra (Program Magister Ilmu Hukum Universitas Ekasakti, 2018)
The provision of remission for corruptors becomes an interesting issue to bediscussed with the issuance of Government Regulation No. 99 of 2012 whose substance isjudged to be contrary to the penal code. The Government Regulation contains severaladditional requirements for special criminal inmates. For prisoners of corruption, thereare two requirements that must be met, namely the general terms and the specialconditions that are applied cumulatively if you want to get a reduction in the period ofdetention. This condition resulted in the increasingly difficult inmates of corruption toobtain remission as happened in Penitentiary Class IIA Padang.